The Roles of Mosquitoes in the Circulation of Monoxenous Trypanosomatids in Temperate Climates - Kostygov, Alexei Y; Malysheva, Marina N; Ganyukova, Anna I; Razygraev, Alexey V; Drachko, Daria O; Yurchenko, Vyacheslav; Agasoi, Vera V; Frolov, Alexander O (Pathogens (Basel, Switzerland), 2022)
Monoxenous (insect-restricted) trypanosomatids are highly diverse and abundant in nature. While many papers focus on the taxonomy and distribution of these parasites, studies on their biology are still scarce. In particular, this concerns trypanosomatids inhabiting the ubiquitous mosquitoes. To shed light on the circulation of monoxenous trypanosomatids with the participation of mosquitoes, we performed a multifaceted study combining the examination of naturally- and experimentally-infected insects using light and electron microscopy and molecular identification of parasites. Our examination of overwintering mosquitoes (genera Culex and Culiseta) revealed that their guts contained living trypanosomatids, which can be spread during the next season. Experimental infections with Crithidia spp. demonstrated that imagines represent permissive hosts, while larvae are resistant to these parasites. We argue that for the parasites with wide specificity, mosquitoes act as facultative hosts. Other trypanosomatids may have specific adaptations for vertical transmission in these insects at the expense of their potential to infect a wider range of hosts and, consequently, abundance in nature.
Keywords: overwintering mosquitoes; Trypanosomatidae; Crithidia; experimental infection; prevalence; facultative host; transmission; specificity; Paratrypanosoma